Supply and Demand: Resident Applications to Program Positions in Plastic Surgery and Our Sister Specialties. Issue 1 (20th October 2022) - Coombs, Demetrius M.; Kwiecien, Grzegorz J.; Sinclair, Nicholas R.; Zins, James E.
Abstract : Background: Previous studies have compared various attributes of independent and integrated resident applicants and identified criteria for a successful match outcome. Few studies have directly examined the relative desirability of various surgical and nonsurgical specialties from the resident's perspective. To address this, the authors analyzed plastic surgery resident applicants and available positions from 2010 through 2018 and compared these data alongside four surgical and five nonsurgical specialties. Methods: In this cross-sectional, retrospective review from the San Francisco Match and National Resident Matching Program, year, number of applicants, available positions, and specialty (integrated or independent plastic, general, or orthopedic surgery; neurosurgery; otolaryngology; anesthesiology; emergency, family, or internal medicine; and pediatrics) were examined. Results: From 2010 through 2018, the number of integrated positions increased by 142%, whereas the number of integrated applicants increased only by 14.5%. The number of available independent positions decreased by 32.6%, whereas the number of independent applicants decreased by 43.9%. All surgical subspecialties demonstrated a decrease in applicants relative to positions (range 9.9% to 24.8%). Unlike the surgical specialties, the nonsurgical fields increased both their number of positions (14% to 57.2%) and number of applicants (2.2% to 44.1%). In particular, applicants to emergency, family, and internal medicine increased dramatically (17% to 44.1%). Conclusions: Applicants to plastic surgery and other surgical residencies changed minimally. The nonsurgical specialties showed a significant increase in the number of applicants, suggesting increasing interest in the nonsurgical fields. Contributing factors may include medical school pressures, lifestyle concerns, and experience with various specialties during medical school. Means of enhancing medical student exposure to plastic surgery are suggested.